2022
DOI: 10.3389/fnins.2021.801791
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles for Hox Proteins in the Last Steps of Neuronal Development in Worms, Flies, and Mice

Abstract: A remarkable diversity of cell types characterizes every animal nervous system. Previous studies provided important insights into how neurons commit to a particular fate, migrate to the right place and form precise axodendritic patterns. However, the mechanisms controlling later steps of neuronal development remain poorly understood. Hox proteins represent a conserved family of homeodomain transcription factors with well-established roles in anterior-posterior (A-P) patterning and the early steps of nervous sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 91 publications
(145 reference statements)
0
7
0
Order By: Relevance
“…In C. elegans , Hox genes ceh-13 , lin-39 , mab-5 , and egl-5 are expressed both in developing and adult MNs ( Figure 2 ). 28 , 71 In mice, Hox genes are expressed in developing mouse MNs, 26 , 72 and we found that their expression persists into adulthood ( Figure 6C ). The sustained Hox expression, from embryo to adult, in specific MNs along the rostrocaudal axis points toward non-canonical roles in the adult nervous system.…”
Section: Discussionmentioning
confidence: 69%
“…In C. elegans , Hox genes ceh-13 , lin-39 , mab-5 , and egl-5 are expressed both in developing and adult MNs ( Figure 2 ). 28 , 71 In mice, Hox genes are expressed in developing mouse MNs, 26 , 72 and we found that their expression persists into adulthood ( Figure 6C ). The sustained Hox expression, from embryo to adult, in specific MNs along the rostrocaudal axis points toward non-canonical roles in the adult nervous system.…”
Section: Discussionmentioning
confidence: 69%
“…In addition to their early roles in progenitor cell specification, cell survival, neuronal migration, axon guidance, and dendrite morphogenesis (Smith et al ., 2024.) , Hox genes also play key roles in the regulation of synapse formation, neuronal terminal identity and neural circuit assembly at late stages (Feng et al ., 2020; Feng et al ., 2021; Philippidou et al ., 2013.) .…”
Section: Discussionmentioning
confidence: 99%
“…At later stages, the Hox genes also play vital roles in neuronal migration and neural circuit formation (Feng et al ., 2021; Hockman et al ., 2019; Kratochwil et al ., 2017; X. Wang et al ., 2013.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence points to the action of HOX genes in regulating and maintaining post-mitotic and post-natal neural identity as well ( Feng et al, 2021 ), demonstrating that HOX expression is not only necessary for developmental patterning, but also strongly influences circuit connectivity and mature neural function. Osseward et al (2021) reported that a k-means clustering approach to divide lumbar neurons from newborn mice revealed that the first major division between neurons did not resolve into neurotransmitter identity, as expected, but instead divided sensory laminae I-III from HOXC10 expressing neurons in laminae IV-X involved in motor control and proprioception ( Osseward et al, 2021 ).…”
Section: Regionalization—the Foundation Of Cell Identitymentioning
confidence: 99%